(untitled) (Semiárida, 2018)
Soil seed bank is the main store of propagules available for maintenance, regeneration and perpetuation of the rangeland plant community. The composition and distribution of such reservoir can be changed by the practice of roller-chopping. The objective of this work was to evaluate the effect of selective roller-chopping on the germinable grass seeds bank from a calden forest region. In line with that, collection of soil samples was performed on both roller-chopped and untreated rangeland areas considering for each of them the following sampling sites: (1) patches composed by only herbaceous plants (open vegetation), (2) patches composed by a mix of herbaceous and woody plants (closed vegetation), and (3) patches composed by only woody plants. Composition and density of grasses of the seed reservoir were determined by the method of direct germination or seedling emergence. For forage species found in this survey, a higher density of seedlings was observed in samples from areas under roller-chopping and of open vegetation. Regarding non-forage species, in contrast, the maximum number of seedlings was observed in samples from areas that were not treated by rollerchopping. The effects of selective rollerchopping on soil seed reservoir will depend on the plant species under consideration, the characteristics of the vegetation patch, the paddock history of use and the rangeland management after the application of roller-chopping. DOI: http://dx.doi.org/10.19137/semiarida.2017(01).27-39